A qualitative study to analyse adverse drug reaction reporting forms - D, Thamizhvani; Brattiya. R, Keerthana; Bhat.C, Ramachandra; C, Stalin (International Journal of Pharmacology and Toxicology, 2016)
Introduction: Adverse reactions to drugs cause increase in the hospital admissions. They also cause increased financial burdens to the patients. They can be reduced by increasing the awareness about adverse drug reactions. ADR reporting can create a database help in this regard. To make ADR reporting effective, good ADR reporting form is needed. This study was started to analyse the existing ADR forms of different countries and identify the possible improvements that can be made.Material and methods: ADR Reporting forms submitted to the Regional Pharmacovigilance Centre were analysed to identify the difficulties faced by the reporters while filling them. ADR reporting forms of different countries were also collected and analysed. Adequacies of these forms were analysed. Based on this qualitative analysis, areas for improvement were identified.Results: Use of generic names, use of abbreviations and incomplete filling up of the details were observed. Options for causality assessment scales, colouring of mandatory details, categorising ADRs as new or old, dates of intake of concomitant drugs were identified as items to be included in the ADR reporting forms in future.Conclusion: As per the study’s findings and other similar studies , dates of the concomitant drugs, categorisation of ADRs (as known or new ), different colours for the mandatory fields, options for causality assessment scales , whether the ADR is medically confirmed , exact chronology of clinical events are the items which can be included in ADR reporting forms in future. Need for more training for primary reporters in filling up of the ADR reporting form is recognized in this study.